2020
DOI: 10.1590/0102-311x00052119
|View full text |Cite
|
Sign up to set email alerts
|

Binge drinking, alcohol outlet density and associated factors: a multilevel analysis among adolescents in Belo Horizonte, Minas Gerais State, Brazil

Abstract: Our study sought to evaluate the prevalence of binge drinking in adolescents and its association with density of alcohol outlets around schools. This cross-sectional study was conducted in Belo Horizonte, Minas Gerais State, Brazil, with 436 high-school students aged between 17 and 19 and enrolled in 18 public and private schools. The students completed the Alcohol Use Disorder Identification Test (AUDIT-C), consisting of questions about alcohol consumption by parents and siblings, and socioeconomic status (ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
(67 reference statements)
2
12
0
2
Order By: Relevance
“…Learners also consumed alcohol at parties, friend’s places, clubs and communities. These findings confirm ease of alcohol access by learners both around schools and in the communities, consistent with studies conducted in South Africa [ 21 , 24 , 31 ] and other countries [ 39 , 59 , 60 ]. Hasheena et al [ 28 ], reported that 62% of grade 8 learners, 81% of grade 10 learners and 92% of grade 12 learners reported that alcohol was easily accessible to them in Namibia.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Learners also consumed alcohol at parties, friend’s places, clubs and communities. These findings confirm ease of alcohol access by learners both around schools and in the communities, consistent with studies conducted in South Africa [ 21 , 24 , 31 ] and other countries [ 39 , 59 , 60 ]. Hasheena et al [ 28 ], reported that 62% of grade 8 learners, 81% of grade 10 learners and 92% of grade 12 learners reported that alcohol was easily accessible to them in Namibia.…”
Section: Discussionsupporting
confidence: 91%
“…Hasheena et al [ 28 ], reported that 62% of grade 8 learners, 81% of grade 10 learners and 92% of grade 12 learners reported that alcohol was easily accessible to them in Namibia. Studies have reported that the more alcohol outlets within school vicinity and in the communities, the more likely youths will engage in drinking alcohol, and this has been reported in countries such as South Africa [ 21 , 24 , 31 ], Namibia [ 39 ], Brazil [ 59 ] and Canada [ 60 ]. Therefore, the wide availability of alcohol outlets around schools and the lack of regulating policies contribute to the normalisation of alcohol use [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among adolescents, alcohol consumption by peer access was reported to be higher with exposure to alcohol outlets [33]. In agreement with Morrison and colleagues, Martins et al [37], in a convenience sampling method, discovered that binge drinking among students often occurs as a result of the density of alcohol outlets near the school; however, the convenience sample was not sufficient enough to be representative [75]. Correspondingly, a cross-sectional study with a randomly drawn sample from Curitiba's public schools conducted by Cardoza et al [41] showed an agreement with the mentioned association between adolescents' consumption and the alcohol outlet density, where it reported that a higher density of alcohol outlets is positively associated with more consumption, and adolescents in schools located further than 250 m away from alcohol outlets were had lower consumption of alcohol.…”
Section: Proximity To Alcohol Outletssupporting
confidence: 83%
“…Among adolescents, alcohol consumption by peer access was reported to be higher with exposure to alcohol outlets [33]. In agreement with Morrison and colleagues, Martins et al [37], in a convenience sampling method, discovered that binge drinking among students often occurs as a result of the density of alcohol outlets near the school; however, the convenience sample was not sufficient enough to be representative…”
Section: Proximity To Alcohol Outletsmentioning
confidence: 67%